ISOLATION AND IDENTIFICATION OF Pseudomonas aeruginosa IN COSMETICS AND PERSONAL CARE PRODUCTS IN IRAQ - RASHEED, MOHAMMED J. (Journal of Duhok University, 2023)
Cosmetics contain varying amounts of nutrients that promote microbial growth. Bacteria such as Pseudomonas aeruginosa, is the most common contaminants in cosmetic products. Water contamination is a likely source of organisms found in cosmetic products. Shampoo, dish washing liquid, facial cleanser, and wet wipes were all tested.Employing rigorous isolation and identification techniques, we aim to elucidate the extent of contamination and assess the potential risks associated with the presence of this microorganism in products intended for routine use. Our research involves the systematic collection of samples from various regions of Iraq, followed by thorough microbiological analyses to accurately isolate and identify Pseudomonas aeruginosa strains. Our study has shown the highest prevalence of Pseudomonas aeruginosa in Shampoo with 3 samples out of 50 samples (6%), whereas the other tested products recorded quite the same results; dishwashing liquid scored 4%, while wet wipes and face cleaner showed 4%. By shedding light on the microbial safety of cosmetics and personal care items, this study contributes valuable insights for regulatory authorities, manufacturers, and consumers, fostering a safer and healthier consumer environment. Culture-based methods demonstrated that reliability in terms of speed, cost-effectiveness, and sensitivity. The current finding was undertaken in response to the extensive cosmetics market and the paramount concern for consumer safety.